At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

What is the resulting equation when the expression for y in the second equation is substituted into the first equation?



3x + y = 1

y = 6 - 4x

a: 7x + 6 = 1
b: -x + 6 = 1
c: x + 6 = 1


Sagot :

3x + y = 1 | Original equation

3x + 6 - 4x = 1 | The expression in the second equation is substituted for y in the first expression.

3x - 4x + 6 = 1 | Rearrange order of operations (commutative property)

-1x + 6 = 1 | Added like terms

b: -x + 6 = 1 | Final equation